Physiological and morphological response to short-term starvation and re-feeding in sub-yearling siberian sturgeon (Acipenser baerii Brandt, 1896): effects of compensatory growth - Ashouri, Gh.; Yavari, V.; Bahmani, M.; Yazdani, M.A.; Kazemi, R.; Morshedi, V.; Fatollahi, M. (2015)
In this study, the capacity of Siberian sturgeon, Acipenser baerii with mean weight 19.3±0.4 g to face short-term starvation and subsequent re-feeding was assessed for a 40-day period. To investigate, the effect of compensatory growth on some physiological response (plasma cortisol, thyroid hormones, glucose, protein, cholesterol and triglyceride) and morphological (total body weight and length, condition factor, hepato-somatic index, vicero-somatic index and digestive-somatic index) in Siberian sturgeon four different feeding regimes were established. Control group fed four times daily to apparent satiation; SRF1: 2 days starvation and 8 days refeeding; SRF2: 4 days starvation and 16 days refeeding; SRF3: 8 days starvation and 32 days refeeding were experienced. At the end of experiment, blood samples were collected to analyze biochemical parameters. Plasma cortisol and thyroxin (T_4) hormones levels were not significantly different between control and food deprived groups at the end of experiment (P>0.05) but plasma tri-iodothyronin (T_3) levels were lower in the starved groups compared to control animals, but this decreases only in S1 group was significant (P<0.05). There were no significant difference in measured metabolites levels between control and food deprived groups (P>0.05). Moreover, at the measured morphometric indices were not observed significantly different between the control and starved groups (P>0.05). The results suggest that Siberian sturgeon has the physiologic and metabolic adjustment ability to shortterm starvation and return to basal level after re-feeding.